RELEVANSI HUKUM ISLAM TERHADAP NILAI-NILAI ADAT MASYARAKAT SIDOJADI DALAM PEMBAGIAN WARISAN - Nasution, Martua; Dongoran, Irham (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This research explores traditional values in the traditional inheritance distribution system carried out by the Sidojadi community in Mandailing Natal Regency from the perspective of Islamic law. So, the research aims to understand how local customary values and traditions coexist with various principles contained in Islamic law regarding the inheritance distribution process. The data found were analyzed using the descriptive-analytical method, namely analyzing primary and secondary data obtained through interviews and literature studies and trying to see the relationship between the two. The results of the research explain that the relationship between the customary inheritance system and the principles of Islamic law which is reflected in the arrangements for the distribution of inheritance in the Sidojadi community, starting from the appointment of heirs, as well as the involvement of traditional institutions in this process has illustrated a very positive thing. Apart from that, the research results also explain that the harmony between traditional values and principles in Islamic law related to the context of inheritance distribution in Sidojadi society is very appropriate.